Interactive effect of thermal environments and bio-regulators on wheat (Triticum aestivum) - LAKHRAN, HANSA; SHARMA, O M PRAKASH; BAJIYA, ROHITASH; CHOUDHARY, MEENA; KANWAR, SUSHILA; CHOUDHARY, JEET RAM (The Indian Journal of Agricultural Sciences, 2022)
Wheat grain yield is affected by several biotic and abiotic factors. Among the abiotic factors heat stress is the most important factor that greatly affects the productivity of wheat. A study was carried out in loamy-sand soil to evaluate the effect of sowing at different thermal environments and its interaction with foliar spray of bio-regulators on growth indices and yield of wheat during rabi 2016–17 and 2017–18 at S K N Agriculture University, Jobner, Jaipur, Rajasthan. The experiment was laid out in a split plot design with four replications consisting of 24 treatments. Wheat sown at 20ºC temperature, reported maximum growth indices i.e. LAD, CGR, RGR and NAR at 30–60 DAS and 60–90 DAS which were significantly higher than D1 (sowing at 18ºC) and D3 (sowing at 22ºC). The significantly higher LAI was recorded under B4 (SA @200 ppm) over all other treatments, while it remained at par with B3, B7 and B8 at 60 DAS and B6 and B8 at 90 DAS. At 30–60 DAS and 60–90 DAS, significantly higher LAD, CGR and RGR were noticed under the treatment B4 (SA @200 ppm) which superseded over rest of the treatments while it remained at par with B8 except CGR at 60–90 DAS. It is concluded that salicylic acid @200 ppm may be sprayed on 20ºC temperature sown crop, plays a major role in mitigating the abiotic stress via creation of favourable micro-climate; thereby increasing the productivity.